Digestibilidade e exigência nutricional de lisina sob o conceito de proteína ideal em dois grupos genéticos de codornas de corte - Fabiana Ferreira (2015)
Five completely randomized experimental designs were carried out to estimate the true ileal digestibility of lysine in diet, digestible lysine requirements of two strains (EV1 and EV2) for performance trait of meat type quails during the initial phase (from hatch to 22 days of age) and for performance and carcass traits during the final phase (from 22 to 35 days of age) of the growth period. In experiment 1 the true lysine digestibility estimates for EV1 and EV2 strains were 94.94% and 88.61% at 21 days of age, respectively. The true lysine digestibility estimates in the final phase (at 35 days of age) for EV1 and EV2 strains were 94.83% and 95.40%, respectively. In experiment 2 the effect of lysine digestible on performance of EV1 strain from hatch to 21 days of age were evaluated. The estimated digestible lysine requirement for weight gain during the initial phase of the growth (from hatch to 21 days of age) is 1.66%. In experiment 3 digestible lysine requirements for EV2 strain in the first phase (from hatch to 21 days of age) of the growth period were evaluated. The estimated digestible lysine requirement for weight gain during the initial phase of the growth period is 1.60%. In experiment 4 digestible lysine requirements for EV1 strain during the final phase of the growth period were estimated. No significant effects of digestible lysine were observed for carcass traits. Higher weights and yields of liver were observed for females, while males showed higher carcass yield. Digestible lysine requirement for maximum quail weight gain of is 1.33% of the diet. In experiment 5 the effects of digestible lysine on performance and carcass traits of EV2 strain from 22 to 35 days of age were evaluated. No significant effects of lysine were observed for carcass traits. Higher weights and yields of liver and gizzard were observed for females, while males showed higher carcass yield. Lysine requirement for maximum quail weight gain is 1.35% of the diet.